Kinetic Modeling of C3H6 Inhibition on NO Oxidation over Pt Catalyst - Muhammad Mufti Azis; Derek Creaser (Bulletin of Chemical Reaction Engineering & Catalysis, 2016)
Exhaust after treatment for lean burn and diesel engine is a complex catalytic system that consists of a number of catalytic units. Pt/Al2O3 is often used as a model Diesel Oxidation Catalyst (DOC) that plays an important role to facilitate oxidation of NO to NO2. In the present study, we proposed a detailed kinetic model of NO oxidation as well as low temperature C3H6 inhibition to simulate temperature-programmed reaction (TPR) data for NO oxidation over Pt/Al2O3. A steady-state microkinetic model based on Langmuir-Hinshelwood mechanism for NO oxidation was proposed. In addition, low temperature C3H6 inhibition was proposed as a result of site blocking as well as surface nitrite consumption. The model can explain the experimental data well over the studied temperature range.